Tourist Preferences, the Use of Social Media, and Travel Behaviours among Youth in Malaysia - Siti Yuliandi Ahmad; Nur Qasdina Asyura Pg Idris (Journal of Advanced Research in Business and Management Studies, 2024)
The tourism sector in Malaysia plays a significant role in driving economic development, with particular emphasis on the youth travel market. The influence of social media on young individuals' travel preferences and behaviours is of considerable importance. However, there still needs to be more understanding of the specific relationship between tourist preferences, social media use, and travel behaviour among youth in Malaysia. This study aims to determine the relationship using a quantitative research design. A cluster sampling technique was used to select a sample of youth in Malaysia. Data were collected through an online survey and analysed using descriptive and inferential statistics Pearson Correlation. The study showed that social media significantly affects young travel behaviour, social media use, and tourist behaviour in Malaysia. The tourist preferences (min=4.352), use of social media (min = 4.005) and travel behaviour (min = 4.238). Pearson Correlation was used to determine the significant relationship between tourist preferences, the use of social media and travel behaviour. The results showed that travel behaviour was positively and significantly correlated with tourist preferences (r = 0.6282, p < 0.01) and the use of social media (r = 0.540, p < 0.01). These results contribute to a better understanding of the relationship between tourist preferences, social media use, and travel behaviour among youth in Malaysia. The findings are also expected to interest tourism marketers and policymakers in developing strategies to attract and retain youth travellers.